2016
DOI: 10.1016/j.bpsc.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Neural Recruitment for Bayesian Adjustment of Inhibitory Control in Methamphetamine Dependence

Abstract: Delineating the processes that contribute to the progression and maintenance of substance dependence is critical to understanding and preventing addiction. Several previous studies have shown inhibitory control deficits in individuals with stimulant use disorder. We used a Bayesian computational approach to examine potential neural deficiencies in the dynamic predictive processing underlying inhibitory function among recently abstinent methamphetamine-dependent individuals (MDIs), a population at high risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 61 publications
4
43
0
Order By: Relevance
“…These outcome-driven signals did however correlate with an unsigned prediction error: how surprising or salient any outcome is based on current expectations. There are an increasing number of studies implicating OFC in modulating salience for the purposes of learning [71][72][73][74]. However, given the precise pattern of OFC signals observed in the current study, the OFC T O2 responses might reflect the acquired salience of an outcome, e.g., refs.…”
Section: Discussionmentioning
confidence: 73%
“…These outcome-driven signals did however correlate with an unsigned prediction error: how surprising or salient any outcome is based on current expectations. There are an increasing number of studies implicating OFC in modulating salience for the purposes of learning [71][72][73][74]. However, given the precise pattern of OFC signals observed in the current study, the OFC T O2 responses might reflect the acquired salience of an outcome, e.g., refs.…”
Section: Discussionmentioning
confidence: 73%
“…Multiple studies and theoretical models have suggested that reward systems contribute to IGD (Brand et al., 2016; Dong, Hu, & Lin, 2013; Dong et al., 2011; Dong & Potenza, 2014). Higher activation of the caudate may relate to increased striatal dopamine synthesis (Harle, Zhang, Ma, Yu, & Paulus, 2016; Perry et al., 2015; van Holst et al., 2017). The positive correlation between caudate activation and self-reported craving suggests that the higher the caudate activates when experiencing gaming cues, the greater the motivation to game.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that both healthy individuals (Ide et al, 2013) and stimulant users (Harlé et al, 2014; Harlé et al, 2016) continuously alter their response strategy in a standard inhibitory paradigm (stop-signal task, SST), such that dynamic fluctuations in their reaction time and performance are consistent with a Bayesian sequential adjustment of their beliefs (Yu and Cohen, 2009) and decision strategy (Shenoy and Yu, 2011). Whereas standard behavioral measures to assess performance in the SST, such as mean stop-signal reaction time (SSRT) or stop signal asynchrony dependent error rate, are relatively easy to obtain, Bayes-optimal model parameters have the advantage that they provide quantitative explanatory measures of an underlying putative cognitive process.…”
Section: Introductionmentioning
confidence: 99%